2002
DOI: 10.1124/dmd.30.1.27
|View full text |Cite
|
Sign up to set email alerts
|

The Disposition, Metabolism, and Pharmacokinetics of a Selective Metabotropic Glutamate Receptor Agonist in Rats and Dogs

Abstract: This paper is available online at http://dmd.aspetjournals.org ABSTRACT:Compound LY354740 [(؉)-2-aminobicyclo[3.1.0]hexane-2,6-dicarboxylic acid], an analog of glutamic acid, is a selective group 2 metabotropic glutamate receptor agonist in clinical development for the treatment of anxiety. Studies have been conducted to characterize the absorption, disposition, metabolism, and excretion of LY354740 in rats and dogs after intravenous bolus or oral administration. Plasma concentrations of LY354740 were measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
20
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 21 publications
5
20
0
Order By: Relevance
“…The lack of further metabolism and the patterns of excretion are similar to previous data for LY354740 (Johnson et al, 2002). Therefore, due to the nearly complete first-pass hydrolysis of LY544344, the pharmacokinetics of the active LY354740 is the best measure of the prodrug's performance in vivo.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The lack of further metabolism and the patterns of excretion are similar to previous data for LY354740 (Johnson et al, 2002). Therefore, due to the nearly complete first-pass hydrolysis of LY544344, the pharmacokinetics of the active LY354740 is the best measure of the prodrug's performance in vivo.…”
Section: Discussionsupporting
confidence: 68%
“…1) is a potent and selective agonist of group II/cAMP-coupled metabotropic glutamate (mGlu2/3) receptors, with anxiolytic activity in numerous animal models (Schoepp et al, 1997(Schoepp et al, , 2003. Although LY354740 is highly soluble and not metabolized in any studied species, its bioavailability ranged from only 10% in rats to 45% in dogs (Johnson et al, 2002) and was similarly low in humans (Kellner et al, 2005). The low systemic availability of LY354740 appears to be due to poor intestinal permeability, related to its low molecular weight, zwitterionic character, and polarity.…”
mentioning
confidence: 99%
“…We report here that LY404039 effectively modulates mGlu2/3 receptors in situ with a potency similar to that previously reported for LY354740, suggesting that this compound should also demonstrate efficacy in animal models of psychosis and anxiety. Perhaps most importantly, we demonstrate here that despite the in vitro similarities between LY354740 and LY404039, oral administration of LY404039 results in much higher plasma levels and bioavailability (63%; Monn et al, 2007) than previously observed following oral administration of LY354740 (ϳ10%; Johnson et al, 2002) and a different pharmacokinetic profile. The mechanism by which LY404039 crosses the gastrointestinal tract is not clearly understood.…”
mentioning
confidence: 74%
“…Interestingly, although similar to LY354740, LY404039 was ϳ2-to 3-fold less potent in this assay. Despite the slightly lower potency of LY404039 versus LY354740 in binding and functional assays, LY404039 demonstrated higher plasma exposure and better oral bioavailability in pharmacokinetic experiments in rats [ϳ63% (see Monn et al, 2007) compared with ϳ10% for LY354740 (Johnson et al, 2002)]. Electrophysiological studies indicated that LY404039 suppressed electrically evoked excitatory activity in the striatum, an effect reversed by the mGlu2/3 receptor antagonist LY341495, indicating that the suppression of neural activity was probably mediated via mGlu2/3 receptors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation